Culture, Faith, and Philanthropy - Ward, J. author. aut Link
XIII, 215 p.
Keywords: Empowered by new wealth and by their faith, early modern Londoners began to use philanthropy to assert their cultural authority in distant parts of the nation. Culture, Faith, and Philanthropy analyzes how disputes between London and provincial authorities over such benefactions demonstrated the often tense relations between center and periphery.